2023
DOI: 10.2147/ijgm.s391312
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the CHA2DS2-VASc Score for In-Stent Restenosis Among Patients with Drug-Eluting Stents Implantation

Abstract: Objective The CHA2DS2-VASc score, a system which has been initially recommended for the assessment of thromboembolic risk in patients with atrial fibrillation (AF), arouses attention in the field of adverse coronary events. The purpose of this study was to explore the predictive value of preprocedural CHA2DS2-VASc score on ISR in patients after drug-eluting stent (DES) implantation. Methods To further investigate the relationship between CHA2DS2-VASc scores and ISR afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A higher CHA2DS2-VASc score indicates a greater number of CKD risk factors and an increased susceptibility to ISR. In recent years, numerous studies have demonstrated that the CHA2DS2-VASc score has predictive value for ISR in various patient populations [2,[5][6][7]. Consistently, this research found that the CHA2DS2-VASc score was an independent risk factor for ISR in patients with SKD.…”
Section: Heart Surgery Forum E129supporting
confidence: 75%
See 2 more Smart Citations
“…A higher CHA2DS2-VASc score indicates a greater number of CKD risk factors and an increased susceptibility to ISR. In recent years, numerous studies have demonstrated that the CHA2DS2-VASc score has predictive value for ISR in various patient populations [2,[5][6][7]. Consistently, this research found that the CHA2DS2-VASc score was an independent risk factor for ISR in patients with SKD.…”
Section: Heart Surgery Forum E129supporting
confidence: 75%
“…The most frequently utilized method for PCI is the insertion of a stent, which is associated with potential complications including stent thrombosis and restenosis [5]. As PCI procedures become more complex and involve multi-ple vessels, ISR is becoming more prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation